Import competition, productivity and multi-product firms - Emmanuel Dhyne; Amil Petrin; Valerie Smeets; Frederic Warzynski (National Bank of Belgium, 2014)
Using detailed firm-product level quarterly data, we develop an estimation framework of a Multi-Product Production Function (MPPF) and analyse firm-product level TFP estimations at various levels (industries, products). After documenting our estimation results, we relate productivity estimates with import competition, using firm and product level measures of import competition. We find that if productivity at the firm level tends to positively react to increased import competition, the multi-product firms response varies according to the relative importance of the product that faces stronger import competition in the firm's product portfolio. When import competition associated to the main product of a firm increases, the firm tend to increase its efficiency in producing that core product, in which it has a productivity advantage. However, when the degree of foreign competition increases for non core products of a firm, it tends to lower its efficiency in producing those goods.
Keywords: D24; L22; L25; 330; multi-product production function; productivity; import competition; Mehrproduktfertigung; Produktionsfunktion; Produktivität; Import; Internationaler Wettbewerb; Industrie; Schätzung; Belgien